2017
DOI: 10.1177/0022034517718532
|View full text |Cite
|
Sign up to set email alerts
|

A New Laser-Processing Strategy for Improving Enamel Erosion Resistance

Abstract: In the present study, a new automatic laser-processing strategy allowing standardized irradiation of natural tooth areas was investigated. The objective was to find a combination of laser parameters that could cause over a 600°C temperature increase at the enamel surface while not damaging enamel, avoiding temperature change above 5.5°C in the pulp and increasing enamel erosion resistance. Seventy-seven bovine enamel samples were randomly divided into 6 laser groups and 1 negative control (C/no treatment/ n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In the present study, an average of 35.7 μm of enamel was lost after 280 min of in situ/in vivo erosion. Similar erosive tooth wear (37.0 μm) was achieved after 72 min of in vitro erosion using citric acid at a similar pH (Esteves-Oliveira et al, 2017). Erosive enamel loss has been reported to increase linearly with time with acidic solution exposure .…”
Section: Discussionmentioning
confidence: 54%
“…In the present study, an average of 35.7 μm of enamel was lost after 280 min of in situ/in vivo erosion. Similar erosive tooth wear (37.0 μm) was achieved after 72 min of in vitro erosion using citric acid at a similar pH (Esteves-Oliveira et al, 2017). Erosive enamel loss has been reported to increase linearly with time with acidic solution exposure .…”
Section: Discussionmentioning
confidence: 54%
“…Currently, strategies for preventing dental erosion include fluoride application, and modification of acidic beverage, and laser irridation, etc. [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that CO 2 laser is very effective for the prevention of tooth decay and dental erosion under previously established parameters in comparison to Er:YAG laser, among other approaches [33][34][35]. However, based on the favorable chemical changes 5 Journal of Spectroscopy observed that could improve the enamel structure, it is suggested that additional studies be carried out to evaluate the acid resistance of enamel for the establishment of alternative preventive protocols and protect areas that are susceptible to caries, such as occlusal surfaces.…”
Section: Discussionmentioning
confidence: 99%